2020
DOI: 10.1097/wnr.0000000000001417
|View full text |Cite
|
Sign up to set email alerts
|

Chicken cognin interactome and the memory of filial imprinting

Abstract: Visual imprinting is a learning process whereby young animals come to prefer a visual stimulus after exposure to it (training). The intermediate medial mesopallium in the domestic chick forebrain is critical for visual imprinting and contributes to molecular regulation of memory formation. Criteria used to infer that a change following training is learning-related have been formulated and published. Cognin (protein disulphide isomerase) is one of several identified plasma membrane and mitochondrial proteins th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Evidence from ablation experiments indicates that both the left and the right IMM have a storage function but that, in addition, the right IMM is necessary for subsequent storage without the IMM, in an, as yet, unidentified region termed S' (Cipolla-Neto et al, 1982 ); as shown in Solomonia et al ( 2000 ) and Tiunova et al ( 2019 ) for possible candidate regions for S'. Learning-related biochemical changes are usually more strongly expressed in the left IMM than in the right IMM, especially 24 h after imprinting (Solomonia and McCabe, 2015 ; see also Margvelani et al, 2018a ; Chitadze et al, 2020 ). The present study provides additional evidence of hemispheric asymmetry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence from ablation experiments indicates that both the left and the right IMM have a storage function but that, in addition, the right IMM is necessary for subsequent storage without the IMM, in an, as yet, unidentified region termed S' (Cipolla-Neto et al, 1982 ); as shown in Solomonia et al ( 2000 ) and Tiunova et al ( 2019 ) for possible candidate regions for S'. Learning-related biochemical changes are usually more strongly expressed in the left IMM than in the right IMM, especially 24 h after imprinting (Solomonia and McCabe, 2015 ; see also Margvelani et al, 2018a ; Chitadze et al, 2020 ). The present study provides additional evidence of hemispheric asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…Several proteins are changed in a learning-related manner following imprinting (reviewed in Solomonia and McCabe, 2015 ). The affected proteins include, among others, cell adhesion molecules, neurotransmitter receptors, protein kinases and their substrates, transcription factors, mitochondrial and membrane proteins, vesicle recycling components, and translation factors (McCabe and Horn, 1988 , 1994 ; Sheu et al, 1993 ; Solomonia et al, 1997 , 1998 , 2000 , 2003 , 2005 , 2008 , 2011 , 2013 ; Meparishvili et al, 2015 ; Margvelani et al, 2018a , b ; Chitadze et al, 2020 ). Further results indicate that neurotransmitter release in the IMM is modulated with memory after imprinting (McCabe et al, 2001 ; Meredith et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autoradiographs were calibrated with protein standards from the P2 mitochondrial-membrane fraction of IMMs of untrained chicks. Four standards (15,30,45, and 60 μg of total protein) were applied to each gel. For regression analysis, the optical density of each band from each sample was divided by the optical density which, from the calibration of the same autoradiograph, corresponded to 30 μg of total protein in the standard [16].…”
Section: Tissue Fractionation For Electrophoresis and Immunoblottingmentioning
confidence: 99%
“…A series of learning-related molecular changes has been, thus, identified in the IMM, changes that are involved in a progression from transient/labile to trophic synaptic modifications, culminating in stable recognition memory [7–16]. These changes occur in proteins involved in cell adhesion, neurotransmitter release, cytoskeletal organization, oxidative phosphorylation, mitochondrial dynamics, local protein synthesis, and others [7–16].…”
Section: Introductionmentioning
confidence: 99%